Penguatan Harmoni Sosial Melalui Moderasi Beragama dalam Surah Al-Kafirun Perspektif Komunikasi Pembangunan (Analisis UINSU “Kampus Moderasi Beragama”) - Nazil Mumtaz al-Mujtahid; Muhammad Alfikri; Solihah Titin Sumanti (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article examines the State Islamic University of North Sumatra's initiative to promote religious development communication, which has made religious moderation the university's identity. This initiative aims to reduce the community's problems with religious extremism and intolerant attitudes. The purpose of this article is to examine communication strategies for religious development that aim to improve social harmony in people's lives. The descriptive analysis method was used in this article, with data collected through direct interviews and observation. The State Islamic University of North Sumatra's communication on religious development takes the form of strengthening human resources through training for lecturers and students, as well as conducting research to implement strategies for improving society. The State Islamic University of North Sumatra has been successful in promoting the value of religious moderation to the university community, as evidenced by an increase in the number of competent human resources in religious moderation and the publication of hundreds of student journals discussing religious moderation. On the other hand, due to a lack of training, the State Islamic University of North Sumatra is still not making efforts to strengthen the value of religious moderation for students, so the value of religious moderation brought by students does not reach a significant value.